Seasonal and Irrigation Rates of Rice Planted as a Repeated Crop after Winter Grain Crops in the Conditions of Light Gray Soils of the Andijan Region - Isashov, Аnvarjon; Khamrokulov, Adakhamjon (European Journal of Life Safety and Stability (2660-9630), 2021)
This article describes the results of scientific research on the introduction of water-saving methods and the introduction of irrigation regimes, one of the main factors in increasing gross production and increasing productivity in rice varieties grown as a secondary crop.